APPLICATION OF FUZZY FMEA TO PERFORM AN EXTENSIVE RISK ANALYSIS IN MARITIME TRANSPORTATION ENGINEERING - Akyuz, Emre (University of Buckingham Press, 2017)
The nature of maritime transportation involves numerous hazards, which can lead to serious consequences for human life, marine environment and ship. Therefore, achieving a high level of safety is recognised as paramount in maritime industry (Akyuz, 2016). In order to achieve this purpose, this paper prompts a fuzzy based Failure Mode and Effects analysis (FMEA) to perform an extensive risk analysis in the maritime transportation industry. The method has capable of identifying potential failures and calculating risk priority number (RPN) by capturing nonlinear casual relationships between the failures. The proposed method is applied to hatch cover failures in operational aspects in bulk carrier ships since potential failures of hydraulic hatch covers have serious concerns for ship owners. Besides its theoretical insight, the paper has practical benefits to ship owners, superintendents as well as safety professionals by identifying potential failure and offering early corrective actions. © 2017: The Royal Institution of Naval Architects.
Keywords: Accident prevention; Risk analysis; Risk assessment; Failure mode and effects analysis; Human lives; Level of safeties; Marine environment; Maritime industry; Maritime transportation; Potential failures; Ship owners; Transportation engineering; Transportation industry; Hatch covers